Answers

2014-10-29T18:41:35+05:30
Let the number be xy
x+y=9...............(1)
(10x+y)+27=10y+x
10x-x+y-10y=-27
9x-9y=-27
x-y=-3................(2)
add equation 1 and 2
we get
x=3
substitute it in eq 1
y=6
so the number is 36
1 5 1
  • Brainly User
2014-10-29T19:45:09+05:30
Let the number be xy.
x + y = 9  =>(1)
(10x + y) + 27 = 10y + x
10x - 10y + y - x = -27
9x - 9y = -27
x - y = -3  =>(2)
adding (1) and (2)
we get, x = 3  =>(3)
substituting (3) in (1)
we get, y = 6
therefore the number is 36.
0